Caregivers with greatest supporting need based on the relationship between personality, overload and coping strategies related to caregivers of dependent patients from the hospitable area Virgen Macarena of Seville - Mª Angustias Navarro Arquelladas (Fundación para el Desarrollo de la Enfermería, 2011)
Objective: Find a relationship between personality, the overhead of caregivers and the coping strategies that develop these to meet the care, allowing us to detect carers need greater supportMaterial and Methods: There has been realized a descriptive study in which there have taken part 23 carer of major dependent persons admitted to the Hospitable Area "Virgen Macarena" of Seville. Demographic and clinical variables have been collected through: general interview, Revised Eysenck Questionnaire of Personality, brief version (EPQ-RA), Coping Strategies Inventory, Zarit Scale Overload.Outcomes: The majority of caregivers are women (86.96%) with an average age of 54.9 years old, with studies of basic education. Among them, 56.52% suffer from some kind of disease and 92.86% of these caregivers have no help. Statistical significance was found for extraversion, neuroticism, pretention-conformity, overload and coping strategies. Conclusions: Caregivers, with high scores on the extroversion scale, perform a proper handling of the situation, while those who obtained higher scores on the neuroticism scale, performed improper handling of the situation.